The seismic signature of rain - Dean, Tim (Society of Exploration Geophysics, 2017)
Rain has long been a problem for land seismic surveys, in terms of its effect on the condition of the surface and near surface, and also due to the seismic noise it creates when raindrops hit the ground. I measured the seismic signature of rainfall using water dripped from height using a pipette and natural rain in Winchester, England, over a three-month period. My results indicated that rain noise is concentrated at frequencies of greater than 80 Hz with a detectable range of less than 1 m. Drops of water landing directly on a geophone result in events with amplitudes nearly 30 times larger than those landing next to the geophone. Items placed on the surface of the ground, such as cables, absorb the energy of the impact and reduce the level of the resulting seismic noise. Burying geophones results in attenuation of rain noise by between 7.7 and 8.6 dB/0.1 m. But, given the effort required to bury geophones, it is likely that data processing algorithms, or the placement of vibration-absorbent matting, are likely to be the preferred strategies for dealing with the noise.